Laminate for highly resistant packaging material
By using acid to modify polyethylene and low-density polyethylene in the adhesive layer of the packaging material and performing surface modification on the metal layer, the problems of adhesive layer peeling and metal corrosion in the face of strong oxidation or strong acid content are solved, and high content resistance and good processing performance are achieved.
Patent Information
- Application Number
- JP2021020003
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-02-10
AI Technical Summary
When existing packaging materials face strong oxidation or strong acidic contents, they are prone to problems such as adhesive layer peeling and metal corrosion, resulting in reduced airtightness and failure of packaging materials.
An adhesive layer composed of acid modified polyethylene and low-density polyethylene is used, and surface modification is performed on the metal layer to form a packaging material with high content resistance.
It improves the resistance of the packaging material to strong oxidation or strong acidic contents, reduces the necking phenomenon of the adhesive layer, improves processing performance, and suppresses the occurrence of wrinkles during heat treatment.
Smart Images

Figure 0007647141000002 
Figure 0007647141000003 
Figure 0007647141000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate that forms a packaging material having excellent resistance to contents, and a method for producing the same. [Background technology]
[0002] 2. Description of the Related Art Conventionally, as packaging materials for packaging foods, medicines, and the like, laminates having gas barrier properties that block the intrusion of water vapor, oxygen, and other gases that deteriorate the contents have generally been used in order to prevent deterioration or spoilage of the contents and to maintain their functions and properties.
[0003] In laminates, even for applications involving resistant packaging materials, two-liquid urethane curing type dry lamination adhesives are generally used as the adhesive that forms the adhesive layer. However, many of the contents packed in the packaging material contain alkaline substances, fragrances, surfactants, high-boiling organic solvents, etc., and packaging these contents can have an adverse effect on the dry lamination adhesive layer, leading to a decrease in the laminate strength of the laminate and sometimes causing peeling.
[0004] In other words, in the case of packaging materials that require resistance to contents, content resistance is required to prevent delamination (peeling) of the package due to the contents, but with conventional dry lamination, there is a problem that the laminate strength between the aluminum foil and the sealant layer decreases over time, resulting in delamination (peeling).
[0005] In order to cope with such a situation, various improvements have been made to the adhesives used in lamination, and those with alcohol resistance have been proposed (for example, Patent Document 1). As an adhesive, a laminate using maleic anhydride grafted modified polyethylene has been proposed as an adhesive that has excellent adhesion to a wide variety of transparent barrier films and aluminum foils and excellent resistance to contents. However, maleic anhydride grafted modified polyethylene has a problem of poor extrusion processability due to its large neck-in during extrusion processing.
[0006] On the other hand, it is known that metal foils such as aluminum foils are corroded by highly acidic or alkaline contents such as hair coloring agents, resulting in the formation of fine pinholes. When pinholes are formed, the barrier properties deteriorate, oxygen penetrates through the pinholes, and the hair coloring agent undergoes spot-like discoloration. For this reason, metal foils such as aluminum foils are subjected to chemical conversion treatment.
[0007] For example, Patent Document 2 discloses a packaging material for hair coloring agents in which an aluminum foil and a sealant film are bonded by extrusion of a thermoplastic resin to prevent delamination caused by the hair coloring agent, and the aluminum foil surface is subjected to a chemical conversion treatment such as a chromate phosphate treatment to prevent corrosion. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 5915710 [Patent Document 2] Patent No. 4945871 Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention aims to provide a laminate applicable to packaging materials for contents that are highly aggressive to packaging materials. Another objective of the present invention is to solve the problem that the maleic anhydride grafted modified polyethylene used in the laminate, which has excellent adhesion to aluminum, has a large melt flow rate (hereinafter abbreviated as MFR) and a large neck-in during extrusion processing, resulting in poor extrusion processability. Another objective of the present invention is to solve the problem that the laminate may wrinkle because a high-temperature heat treatment is required to develop adhesive strength. [Means for solving the problem]
[0010] In order to solve the above problems, the present invention provides a highly resistant packaging laminate, which is characterized in that from the surface layer side, a base layer, a metal layer, an adhesive layer, and a thermoplastic resin layer are laminated in this order, the metal layer having a surface modification layer at least on the surface facing the adhesive layer, the adhesive layer containing at least acid-modified polyethylene and low-density polyethylene, and is a melt co-extruded layer in which the acid-modified polyethylene layer is disposed on the metal layer side and the low-density polyethylene layer is disposed on the thermoplastic resin layer side, and which is sandwich-laminated with the base layer, metal layer, and thermoplastic resin layer.
[0011] According to the above-mentioned highly resistant packaging laminate, acid-modified polyethylene and low-density polyethylene are used as an adhesive layer between a metal layer and a thermoplastic resin layer, which are affected by the contents, and the acid-modified polyethylene layer is arranged on the metal layer side, thereby obtaining resistance to the contents. Furthermore, by arranging the low-density polyethylene layer on the thermoplastic resin layer side of the adhesive layer, neck-in during melt co-extrusion can be reduced, thereby obtaining a highly resistant packaging laminate that is highly processable, and that has a surface modification layer on the surface of the metal layer facing the adhesive layer, which can be used as a packaging material for contents that strongly attack the packaging material.
[0012] In the highly resistant packaging laminate, it is preferable that the acid-modified polyethylene layer is made of maleic anhydride graft-modified polyethylene and the thermoplastic resin layer is made of linear low-density polyethylene, which can further improve the content resistance and adhesiveness, and further improve the processability.
[0013] In the highly resistant packaging laminate, the maleic anhydride-grafted modified polyethylene preferably contains a component that shows a first melting point peak at 90° C. to 100° C. in differential scanning calorimetry, and a second melting point peak that continues for 20° C. or more on the lower temperature side from 50° C. Adhesive strength is developed at a lower temperature, and the occurrence of wrinkles during heat treatment can be suppressed.
[0014] In the highly resistant laminate for packaging material, the maleic anhydride graft ratio of the maleic anhydride grafted modified polyethylene is 0.1 wt % or more and 1.0 wt % or less, and the density is 0.88 g / cm 3More than 0.90g / cm 3 It is preferable that the melt flow rate is 8.5 or more and 12.0 or less, because this allows the formation of a film with higher smoothness during the formation of the adhesive layer.
[0015] In the highly resistant packaging laminate, the maleic anhydride grafted modified polyethylene preferably contains a component that shows a broad first melting point peak at about 100°C and a second melting point peak consisting of two consecutive peaks between 110°C and 130°C in differential scanning calorimetry.
[0016] In the highly resistant laminate for packaging material of the preceding paragraph, the maleic anhydride grafted modified polyethylene has a maleic anhydride grafting ratio of 0.1 wt% or more and 1.0 wt% or less, and a density of 0.90 g / cm 3 More than 0.92g / cm 3 It is preferable that the melt flow rate is 5.5 or more and 7.5 or less, because this allows the formation of a film with higher smoothness during the formation of the adhesive layer.
[0017] In the highly resistant packaging laminate, the layer thickness ratio of the melt co-extrusion of maleic anhydride-grafted polyethylene and low-density polyethylene in the adhesive layer is preferably 25:75 to 75:25, which can effectively reduce neck-in and can reduce the amount of expensive maleic anhydride-grafted polyethylene used.
[0018] In the highly resistant packaging laminate, the linear low density polyethylene has a density of 0.915 g / cm 3 More than 0.940g / cm 3 It is preferable that the following is true:
[0019] In the highly resistant packaging laminate, the low density polyethylene has a density of 0.910 g / cm 3 More than 0.930g / cm 3 and the melt flow rate is 6.0 to 8.5. It is preferable that the temperature is lower than the above range. Effect of the Invention
[0020] According to the present invention, a highly resistant laminate for packaging can be obtained that has high resistance to contents and can be applied to packaging for contents that strongly attack the packaging, such as hair coloring agents, hypochlorous acid water, fragrances, etc. In addition, by making the adhesive layer contain acid-modified polyethylene and low-density polyethylene, it is possible to reduce neck-in during melt coextrusion lamination and also to suppress the occurrence of wrinkles during heat treatment, thereby improving processability. [Brief description of the drawings]
[0021] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of a highly resistant packaging laminate of the present invention. [Diagram 2] FIG. 1 is a diagram showing an example of DSC measurement of maleic anhydride-grafted modified polyethylene. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the embodiment described below.
[0023] Fig. 1 is a schematic cross-sectional view of one embodiment of the highly resistant packaging laminate of the present invention. The laminate 1 of this embodiment is configured by sequentially laminating at least a substrate layer 2, an adhesive layer 4, a metal layer 5, an adhesive layer 9 including an acid-modified polyethylene layer 6 and a low-density polyethylene layer 7, and a thermoplastic resin layer 8. A modified treatment layer 10 is formed on the surface of the metal layer 5 facing the adhesive layer 4. A printing ink layer 3 can be provided on the substrate layer 2.
[0024] The resin forming the base layer 2 may be a polyester-based resin, polyamide-based resin, polyolefin-based resin, etc., which are commonly used in this type of packaging material. For example, polyester-based resins include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyethylene-2,6-naphthalate, polybutylene terephthalate, and copolymers thereof.
[0025] The thickness of the base layer 2 is not particularly limited, but a stretched film obtained by biaxial stretching is usually used, and a thickness in the range of 9 μm to 50 μm is preferable. The base layer may be a single layer using only one of the above-mentioned materials, or a multilayer using two or more materials.
[0026] The printed ink layer 3 is not essential, but when necessary to display information on the laminate or pouch, it can be provided by printing with a known gravure ink or the like, although there are no particular limitations thereon.
[0027] Although not shown in Fig. 1, the base layer 2 and the metal layer 5 are laminated via an adhesive. There are no limitations on the adhesive as long as it is a commonly used adhesive. For example, a two-component curing urethane adhesive is preferably used.
[0028] The metal layer 5 is a layer made of metal foil, and aluminum, copper, iron, stainless steel, etc. can be used as the material of the metal foil, but aluminum or an aluminum alloy is particularly preferable from the viewpoint of versatility and flexibility. Furthermore, the thinner the metal foil, the more likely it is that pinholes will occur, so the thickness is preferably 5 μm to 50 μm to ensure the necessary barrier properties.
[0029] When the packaging bag is to have dead-hold properties in order to prevent oxygen from entering through an airbag that occurs after the contents are pushed out and discharged, it is more preferable that the thickness of the aluminum foil is 12 μm or more.
[0030] The surface modification layer 10 is provided to prevent corrosion and delamination of the metal layer 5 when strongly alkaline liquids such as monoethanol and ammonia used in hair colorants, hypochlorites used in cleaning agents, sodium hydroxide, etc., organic solvents such as esters and terpenes in fragrance concentrates, fragrance ingredients such as limonene and menthol, or high-concentration alcohols penetrate the metal foil that constitutes the metal layer 5 from the content side, which can cause the metal layer 5 to corrode and delaminate.
[0031] The surface modification layer 10 is preferably a layer consisting of an inorganic film containing a metal such as zirconium, chromium, titanium, hafnium, or any of its salts, and an organic polymer film covering the inorganic film. The inorganic film can be provided on the metal foil by appropriately adopting a known coating method, such as a zirconium-based chemical conversion coating treatment agent (Surfcoat EC1000A (manufactured by Nippon Paint Surf Chemicals)) or a chromium-based chemical conversion coating treatment agent (Surfcoat NR-X (same as above)), but is not limited thereto. The organic polymer film can be, for example, an acrylic resin, a polyester resin, a phenolic resin, or the like.
[0032] Examples of resins constituting the thermoplastic resin layer 8 include linear low-density polyethylene, polyethylene, polypropylene, epoxy resin (EP), ethylene-vinyl acetate copolymer, ethylene-methacrylic acid copolymer, ethylene-methacrylic acid ester copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, and metal cross-linked products thereof. Among these, linear low-density polyethylene is preferred. These thermoplastic resins may be used alone or in combination of two or more.
[0033] Here, the acid-modified polyethylene layer 6 and the low-density polyethylene layer 7 are laminated by melt coextrusion. The base material layer 2, the printing ink layer 3, the adhesive layer 4, the metal layer 5, and the thermoplastic resin layer 8 are laminated and bonded by sandwich lamination. Here, the modification treatment layer 10 formed on the metal layer 5 and the maleic anhydride grafted modified polyethylene layer 6 are laminated so as to be in contact with each other. With this configuration, the adhesive strength between the metal layer and the adhesive layer is improved, and the adhesive strength can be maintained even after long-term storage by suppressing delamination due to attack caused by penetration of contents.
[0034] Maleic anhydride grafted polyethylene is one of the acid-modified polyethylenes that is preferably used in the present invention. Maleic anhydride grafted polyethylene is polyethylene obtained by grafting polyethylene with maleic anhydride. The maleic anhydride grafted polyethylene used in the present invention preferably contains a component that shows a first melting point peak at 90°C to 100°C and a second melting point peak that continues from 50°C to the lower side by 20°C or more when differential scanning calorimetry (DSC measurement) is performed, as shown in Figure 2.
[0035] By making the resin have a second melting point peak on the low temperature side, adhesiveness is exhibited at a low temperature, so that the occurrence of wrinkles during heat treatment can be suppressed.
[0036] The maleic anhydride graft ratio of the maleic anhydride grafted modified polyethylene is preferably 0.1 wt% or more and 1.0 wt% or less. If it is less than 0.1 wt%, it is likely to lead to a decrease in laminate strength, and if it exceeds 1.0 wt%, it will absorb a lot of moisture, leading to foaming, which may cause high costs and yellowing. It may also be easily absorbed by the extruder or die metal, which may cause discoloration and reduce processability.
[0037] In addition, the layer thickness ratio of the melt co-extrusion of maleic anhydride grafted polyethylene and low density polyethylene in the adhesive layer 9 is preferably 25:75 to 75:25. If the ratio of maleic anhydride grafted polyethylene 6 is less than 25:75, the adhesiveness may become unstable. If the ratio of low density polyethylene 7 is less than 75:25, the neck-in improvement effect may be lost. In addition, if the ratio of maleic anhydride grafted polyethylene is too high, the price is about four times higher than that of general extrusion resins, which is also disadvantageous in terms of cost.
[0038] The highly resistant laminated film for packaging materials of the present invention can be produced by disposing an adhesive layer between a laminate having a base layer 2 and a metal layer 5 and a thermoplastic resin layer 8, with the acid-modified polyethylene layer 6 on the metal layer side and the low-density polyethylene layer 7 on the thermoplastic resin layer side, and melt-co-extruding the layers together, and sandwich-laminating the base layer, the metal layer and the thermoplastic resin layer. As described above, it is preferable to melt-co-extrude the layers so that the layer thickness ratio of the acid-modified polyethylene layer 6 and the low-density polyethylene layer 7 to be melt-co-extruded is 25:75 to 75:25. EXAMPLES
[0039] The present invention will be described in more detail below with reference to examples. The results of each example and comparative example are summarized in Tables 1 and 2.
[0040] <Example 1> (material) In Example 1, the following materials were used: Substrate: Polyester film (thickness 12 μm, FE2001, manufactured by Futamura Chemical Co., Ltd.) Adhesive: Aliphatic ester urethane adhesive, base agent (A525, Mitsui Chemicals, Inc.), hardener (A52, Mitsui Chemicals, Inc.) Metal layer: Aluminum base material (thickness 9 μm, 1N30, manufactured by Toyo Aluminum Co., Ltd.) Surface modification layer: Coating agent containing zirconium compound and organic polymer coating material, Surfcoat EC1000A / B Nippon Paint Surf Chemicals ·Adhesive layer Maleic anhydride grafted polyethylene (M605, manufactured by Mitsubishi Chemical Corporation, first melting point peak 98°C, second melting point peak 50°C, density 0.88g / cm 3 , MFR10g / cm 3 ) Low-density polyethylene (LC600A, manufactured by Nippon Polyethylene Co., Ltd., melting point 106°C, density 0.918g / cm 3 , MFR7.0g / cm 3 ) Thermoplastic resin layer: (linear low-density polyethylene, MTNST, Futamura Chemical Co., Ltd., film thickness 40 μm)
[0041] (Laminate) First, the substrate and the metal layer are laminated via an adhesive, and then a cellulose acetate sheet having a solid content of about 10 mg / m is laminated on the surface of the metal layer opposite to the surface on which the substrate is laminated. 2 The surface modification layer coating liquid was applied so that the surface modification layer was formed. Next, the maleic anhydride grafted polyethylene and low density polyethylene of the adhesive layer were melt-extruded to a thickness of 10 μm each in the direction in which the maleic anhydride grafted polyethylene was laminated on the surface on which the surface modification layer of the metal layer was formed, and sandwich laminated in the order of the substrate, metal layer, adhesive layer, and thermoplastic resin layer. After lamination, the laminate was heated at 140 ° C for 15 seconds while being held by a heater roll to produce a laminate.
[0042] Check neck-in The T-die width used during melt co-extrusion was 360 mm (air gap 120 mm), and the resin width after extrusion was 303 mm. For reference, when a single layer of M605 was used without using low-density polyethylene in the adhesive layer, the resin width after extrusion was 253 mm, confirming that neck-in can be improved by melt co-extrusion of low-density polyethylene.
[0043] (Pouch) The laminate thus prepared was sealed at its edges to form a three-sided pouch, which was then filled with the following contents and subjected to a storage test. Contents: 1: Hair color 1 agent ·Contents 2: Fragrance stock solution Storage conditions: Temperature 50°C, humidity not controlled. Storage period: Four conditions: immediately after (0 days), 1 month (30 days), 2 months (60 days), and 3 months (90 days).
[0044] (evaluation) After storage, a test sample with a width of 15 mm was cut out from the pouch, and the adhesive strength between the metal layer and the adhesive layer (based on JIS K7127) was measured at a tensile speed of 300 m / min. Measuring instrument: RTF-1250 (manufactured by A&D Co., Ltd.)
[0045] <Comparative Example 1> A three-sided pouch was produced using the same laminate structure as in Example 1, except that no surface modification layer was provided. The contents, storage conditions, and evaluation were the same as in Example 1.
[0046] <Comparative Example 2> A three-sided pouch was produced using the same laminate structure as in Example 1, except that a surface modification layer was not provided, the adhesive layer was made of the following material, and the substrate, adhesive, metal layer, adhesive layer, and thermoplastic resin layer were laminated in that order by dry lamination. Adhesive: Ester-based urethane adhesive, base agent (LX500, manufactured by DIC Graphics Co., Ltd.), hardener (KW75, manufactured by DIC Graphics Co., Ltd.) The contents, storage conditions, and evaluation were the same as in Example 1.
[0047] The evaluation results are shown in Table 1.
[0048] [Table 1]
[0049] As is clear from Table 1, the laminate of the present invention showed no decrease in adhesive strength even after storage of contents with strong attacks, and showed good results. On the other hand, the adhesive strength of the comparative example was significantly decreased. Oh no. The invention as originally claimed is set forth below. [1] A highly resistant packaging laminate comprising a base layer, a metal layer, an adhesive layer and a thermoplastic resin layer laminated in this order from the surface side, the metal layer having a surface modification layer at least on the surface facing the adhesive layer, the adhesive layer containing at least acid-modified polyethylene and low-density polyethylene, and being a melt co-extruded layer in which the acid-modified polyethylene layer is disposed on the metal layer side and the low-density polyethylene layer is disposed on the thermoplastic resin layer side, and being sandwich-laminated with the base layer, metal layer and thermoplastic resin layer. [2] 2. The highly resistant laminate for packaging materials according to item 1, wherein the acid-modified polyethylene layer is made of maleic anhydride-grafted polyethylene, and the thermoplastic resin layer is made of linear low-density polyethylene. [3] Item 3. The highly resistant laminate for packaging materials according to item 2, wherein the maleic anhydride-grafted polyethylene contains a component that shows a first melting point peak at 90°C to 100°C and a second melting point peak that continues from 50°C to the lower temperature side by 20°C or more in differential scanning calorimetry. [4] The maleic anhydride grafted polyethylene has a maleic anhydride grafting ratio of 0.1 wt% to 1.0 wt% and a density of 0.88 g / cm 3 More than 0.90g / cm 3 Item 4. The highly resistant laminate for packaging materials according to item 2 or 3, characterized in that the melt flow rate is 8.5 or more and 12.0 or less. [5] Item 3. The highly resistant laminate for packaging materials according to item 2, wherein the maleic anhydride-grafted modified polyethylene contains a component that shows a broad first melting point peak at about 100°C and a second melting point peak consisting of two consecutive peaks between 110°C and 130°C in differential scanning calorimetry. [6] The maleic anhydride grafted polyethylene has a maleic anhydride grafting ratio of 0.1 wt% to 1.0 wt% and a density of 0.90 g / cm 3 More than 0.92g / cm 3 Item 6. The highly resistant laminate for packaging materials according to item 2 or 5, characterized in that the melt flow rate is 5.5 or more and 7.5 or less. [7] 7. The highly resistant laminate for packaging materials according to any one of items 2 to 6, wherein the layer thickness ratio of the melt co-extruded maleic anhydride grafted polyethylene and the low-density polyethylene in the adhesive layer is 25:75 to 75:25. [8] The linear low density polyethylene has a density of 0.915 g / cm 3 More than 0.940g / cm 3 Item 8. The highly resistant laminate for packaging material according to any one of items 2 to 7, characterized in that: [9] The low-density polyethylene has a density of 0.910 g / cm3 or more and 0.930 g / cm 3 Item 9. The highly resistant laminate for packaging material according to any one of items 1 to 8, characterized in that the melt flow rate is 6.0 or more and 8.5 or less. [Explanation of symbols]
[0050] 1. Laminate 2...Base material layer 3. Printing ink layer 4...Adhesive layer 5...metal layer 6. Acid-modified polyethylene layer 7. Low density polyethylene layer 8...Thermoplastic resin layer 9...adhesive layer 10. Surface modification layer
Claims
1. A substrate layer, a metal layer, an adhesive layer, and a thermoplastic resin layer are laminated in this order from the surface layer side, the metal layer has a surface modification layer at least on the surface of the adhesive layer side, the adhesive layer contains at least an acid-modified polyethylene and a low-density polyethylene, and is a melt-coextruded layer in which the acid-modified polyethylene layer is disposed on the metal layer side and the low-density polyethylene layer is disposed on the thermoplastic resin layer side, and is sandwich-laminated with the substrate layer, the metal layer, and the thermoplastic resin layer, 1. A highly resistant laminate for packaging materials, wherein the acid-modified polyethylene layer is made of maleic anhydride-grafted polyethylene, and the thermoplastic resin layer is made of linear low-density polyethylene.
2. The highly resistant packaging laminate according to claim 1, characterized in that the maleic anhydride grafted modified polyethylene contains a component that shows a first melting point peak at 90°C to 100°C in differential scanning calorimetry and a second melting point peak that continues from 50°C to the lower temperature side by 20°C or more.
3. The maleic anhydride grafted polyethylene has a maleic anhydride grafting ratio of 0.1 wt % or more and 1.0 wt % or less and a density of 0.88 g / cm 3 0.90g / cm or more 3 3. The highly resistant laminate for packaging materials according to claim 1 or 2, characterized in that the melt flow rate is 8.5 or more and 12.0 or less.
4. The highly resistant packaging laminate according to claim 1, characterized in that the maleic anhydride grafted modified polyethylene contains a component that shows a broad first melting point peak at about 100°C and a second melting point peak consisting of two consecutive peaks between 110°C and 130°C in differential scanning calorimetry.
5. The maleic anhydride grafted polyethylene has a maleic anhydride grafting ratio of 0.1 wt % or more and 1.0 wt % or less and a density of 0.90 g / cm 3 0.92g / cm or more 3 5.5 or less, and a melt flow rate is 5.5 or more and 7.5 or less.
6. 6. The highly resistant packaging laminate according to any one of claims 1 to 5, characterized in that the layer thickness ratio of the melt co-extruded maleic anhydride grafted modified polyethylene and the low density polyethylene in the adhesive layer is 25:75 to 75:
25.
7. The linear low density polyethylene has a density of 0.915 g / cm 3 0.940g / cm or more 3 7. The highly resistant laminate for packaging material according to claim 1, wherein:
8. The low-density polyethylene has a density of 0.910 g / cm3 or more and 0.930 g / cm3 or more. 3 8.5 or less, and a melt flow rate is 6.0 or more and 8.5 or less.
Citation Information
Patent Citations
JP1974045871A
Pulse combustion device
JP1984015710A
Production of laminated body
JP1989027922A
Laminate and its manufacturing method
JP2004074419A
Multilayer film
JP2010046863A